English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

trying to get a general idea of how to do these because i will take this next year in the ninth grade.

2006-11-05 13:42:09 · 4 answers · asked by miko 1 in Science & Mathematics Mathematics

4 answers

if by this you mean

x^2 - 2x - 2 = 0

x^2 - 2x = 2
x^2 - 2x + 1 = 3
(x - 1)^2 = 3
x - 1 = sqrt(3)
x = 1 ± sqrt(3)

-------------------------

but if you mean

7x^2 - 2x - 2 = 0
7x^2 - 2x = 2
x^2 - (2/7)x = (2/7)
x^2 - (2/7)x + (1/49) = (63/49)
(x - (1/7))^2 = (9/7)
x - (1/7) = (3/7)sqrt(7)
x = (1/7) ± (3/7)sqrt(7)
x = (1/7)(1 ± 3sqrt(7))

2006-11-05 15:35:18 · answer #1 · answered by Sherman81 6 · 0 0

7^2 -2x - 2 = 0 did you mean x^2 instead of 7^2?

x^2-2x-2=0
x^2-2x+1-3=0
(x-1)^2-3=0
x-1=+/-sqrt(3)
x=1+/-sqrt(3)

2006-11-05 21:47:10 · answer #2 · answered by yupchagee 7 · 0 0

http://www.purplemath.com/modules/sqrquad.htm

2006-11-05 21:44:33 · answer #3 · answered by Roman Soldier 5 · 0 0

7^2-2X-2=0
49-2X-2=0
47-2X=0
-2X=-47
X=-47/-2
X=23.5

2006-11-05 21:49:52 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers